MEMBANGUN PRESTASI SEKOLAH MELALUI BENCHMARKING TEKNOLOGI TEPAT GUNA: STUDY KASUS SMK PGRI SUBANG - Abdullah Abdullah; Nurudin Nurudin; Syaefuddin Syaefuddin (LPPM Bunga Bangsa Cirebon, 2021)
This best practice is motivated by complex issues, among others, SMK PGRI Subang is the only SMK PGRI Subang in Subang Regency that has an ISO certificate. In addition, the education unit level curriculum document as a reference in the implementation of learning and education is fully structured. This can be seen from the learning evaluation documents and assessments that are completely administered. Likewise with the conditions and characteristics of students, most of whom have UN scores according to school quality standards. To form a school that excels, the school is improving in every way. One of the efforts made is to apply the